Pembuatan Teknologi Tepat Guna Spinner sebagai Alat Alternatif Peniris Minyak - Cantikasari, Sugma; Wahyu Ali Mashuri, Dandy; Ella Mustika , Elit; Tarigan, Elkana Yolanda; Bintang Rafi, Ken; Firdaus Setiawan, Risqi (EDUPEDIA Publisher, 2022)
Mushrooms are one of the many plant commodities consumed and cultivated by Indonesian people. Crispy mushroom is a processed product of UMKM KWT Sri Rejeki which is in great demand by consumers. This production activity continues to experience development by facing various kinds of obstacles that occur, one of which is in the packaging process where the packaged mushrooms release residual frying oil so that they require Appropriate Technology (TTG) in the form of a spinner or oil drainer. So that KKN-T Group 29 students from Universitas Pembangunan Nasional